Risk factors of esophagojejunal anastomotic leakage after total gastrectomy for gastric and Siewert type II/III esophagogastric cancer: a retrospective analysis from a tertiary hospital - Liu, Junjie; Hu, Jinzhi; Fang, Jiaming; Chen, Yingliang; Chen, Yonghe; He, Jiasheng; Deng, Zijian; Peng, Junsheng; Lian, Lei; Chen, Shi (Frontiers in Oncology, 2024)
Background and objectivesTo detect the risk factors associated with esophagojejunal anastomotic leakage (EJAL) after total gastrectomy for gastric and Siewert type II/III esophagogastric cancer.MethodsThe data for 609 patients underwent Roux-en-Y esophagojejunostomy after total gastrectomy between March 2015 and March 2021 were reviewed. Univariate and multivariate analyses were performed to evaluate the risk factors.ResultsEJAL was observed in 48 (7.9%) of 609 patients. Univariate analysis revealed that gender, the number of comorbidities (hypertension, diabetes mellitus, coronary heart disease and chronic obstructive pulmonary disease), postoperative serum albumin, tumor location, duration of operation were risk factors associated with EJAL. Patients who had the following factors including male, the number of comorbidities ≥2, postoperative serum albumin <35 g/L, tumor location was esophagogastric junction, duration of operation ≥260 min were more likely to develop EJAL than those who had not. Multivariate analysis revealed that the number of comorbidities (OR 3.464, 95% CI 1.178 – 10.189, p = 0.024) and duration of operation (OR 2.657, 95% CI 1.242 – 5.685, p = 0.012) were independent risk factors associated with EJAL.ConclusionsMore morbidities and prolonged operative duration were independently associated with EJAL after total gastrectomy for gastric and Siewert type II/III esophagogastric cancer. This study indicated the necessity for careful management of these high-risk patients.